2008
DOI: 10.1116/1.2839855
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of nanoscale multilayer CrN/NbN physical vapor deposition coatings by high power impulse magnetron sputtering

Abstract: Nanoscale multilayer CrN/NbN PVD coatings are gaining reputation for their high corrosion and wear resistance. However the CrN/NbN films deposited by ABS TM (Arc Bond Sputtering) technology have some limitations such as macro droplets, porosity and less dense structures.The novel HIPIMS (High Power Impulse Magnetron Sputtering) technique produces macroparticle free, highly ionised metal plasma which brings advantages in both surface pretreatment and coating deposition stages of the PVD process.In this study, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 29 publications
4
52
1
Order By: Relevance
“…As-deposited coatings resistance as compared to monolithic coatings [13,23]. The thickness of consecutive layers of CrN and NbN is defined as the bi-layer thickness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As-deposited coatings resistance as compared to monolithic coatings [13,23]. The thickness of consecutive layers of CrN and NbN is defined as the bi-layer thickness.…”
Section: Resultsmentioning
confidence: 99%
“…The capability of CrN/NbN coatings with droplet defects produced by arc etching followed by unbalanced magnetron sputtered (UBM) deposition in resisting oxidation [24], and that of coatings with superior microstructure produced by combined HIPIMS-UBM technique in resisting room temperature wet corrosion and tribo-corrosion has been documented earlier [23,24]. The main objective of this work was the evaluation of the oxidation behaviour of defect free (droplet free and dense structures) CrN/NbN coatings produced by HIPIMS technique on P92 steel at high temperature and wet corrosive conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the corrosion and tribological performances of CrN/NbN coatings (deposited by Arc or conventional magnetron sputtering techniques) have already been investigated [21,22,31,32]. The benefits of using HIPIMS over conventional PVD to deposit CrN/NbN have been also demonstrated [16,33,34]. However, the impact of defects on the coating performance of HIPIMS deposited CrN/NbN was understudied and so far, very little attention was given towards the coatings defects associated with HIPIMS.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the corrosion properties of multilayer PVD coatings depend on their chemical composition, stress level, porosity and thickness as well as on the morphological defects of the coatings [7,16,[20][21][22]34]. To study the effect of the defects on corrosion performance of CrN/NbN nano-scale multilayer coatings, electrochemical corrosion tests were conducted.…”
Section: Electrochemical Corrosion Testmentioning
confidence: 99%